Associations Between Poor Sleep Quality, Anxiety Symptoms, and Depressive Symptoms Among Chinese Adolescents Before and During COVID-19: A Longitudinal Study - Wang, Wanxin; Guo, Yangfeng; Du, Xueying; Li, Wenyan; Wu, Ruipeng; Guo, Lan; Lu, Ciyong (Frontiers in Psychiatry, 2022)
Since the novel coronavirus disease 2019 (COVID-19) outbreak, adolescents' emerging mental health and behavior issues have been an international public health concern. This longitudinal study aimed to examine the situation of poor sleep quality, anxiety, and depressive symptoms among Chinese adolescents and to explore the associations between them before and during COVID-19. A total of 1,952 middle and high school students as eligible participants at baseline (pre-COVID-19, Wave 1; response rate: 98.79%), 1,831 eligible students were followed up at Wave 2 (October 2019 to December 2019, pre-COVID-19; retention rate: 93.80%), and 1,790 completed the follow-up at Wave 3 (during the COVID-19; retention rate: 97.80%). The mean age of the baseline students was 13.56 (SD: 1.46) years. The differences in anxiety and depressive symptoms between Wave 1, Wave 2, and Wave 3 were not statistically significant. The proportion of students with poor sleep quality increased over time, from Wave 1 (21.0%) to Wave 3 (26.0%, OR = 1.37, 95% CI = 1.17–1.60, P = 0.001) and from Wave 2 (21.9%) to Wave 3 (OR = 1.29, 95% CI = 1.11–1.51, P < 0.001). The cross-lagged generalized linear mixed models revealed that the concurrent and cross-lagged associations of poor sleep quality with anxiety symptoms across the three waves were significant (P < 0.05) and vice versa. Only a marginally significant positive cross-lagged association between poor sleep quality at Wave 2 and depressive symptoms at Wave 3 was found (standardized β estimate = 0.044, SE = 0.022, P = 0.045). Sleep quality was adversely affected during COVID-19, and the bidirectional associations of poor sleep quality with anxiety symptoms could not be neglected.